T cell immunotherapy enhanced by designer biomaterials. (October 2019) - Dunn, Zachary S.; Mac, John; Wang, Pin
Abstract: Cancer immunotherapy has recently burst onto the center stage of cancer treatment and research. T lymphocyte adoptive cellular transfer (ACT), a form of cancer immunotherapy, has spawned unprecedented complete remissions for terminal patients with certain leukemias and lymphomas. Unfortunately, the successes have been overshadowed by the disappointing clinical results of ACT administered to treat solid tumors, in addition to the toxicities associated with the treatment, a lack of efficacy in a significant proportion of the patient population, and cancer relapse following the treatment. Biomaterials hold the promise of addressing these shortcomings. ACT consists of two main stages – T lymphocyte ex vivo expansion followed by reinfusion into the patient – and biomaterials can improve the efficacy of ACT at both stages. In this review, we highlight recent advances in the use of biomaterials for T lymphocyte adoptive cellular cancer immunotherapy and discuss the challenges at each stage.